2022
DOI: 10.1101/2022.08.11.503634
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mouse SAS-6 is required for centriole formation in embryos and integrity in embryonic stem cells

Abstract: Cell division fidelity is crucial for stem cell propagation and the maintenance of pluripotency. Centrosomes, which organize the mitotic spindle microtubules to ensure proper bipolar cell division, have a core of a pair of centrioles that duplicate once per cell cycle. At the onset of centriole biogenesis, SAS-6 forms a cartwheel structure, which is the precursor for the forming procentrioles. SAS-6 is essential for centriole formation in human cell lines and other organisms. However, the functions of SAS-6 in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…This may mean that formation of the first centrioles during early embryonic development in cattle can occur despite SASS6 protein deficiency. Structurally similar individual triplets that do not form centrioles were also found upon loss of SASS6 in mouse embryonic stem cells in vitro [57].…”
Section: What Was Found At Division Poles Of Bovine Blastomeres?mentioning
confidence: 71%
“…This may mean that formation of the first centrioles during early embryonic development in cattle can occur despite SASS6 protein deficiency. Structurally similar individual triplets that do not form centrioles were also found upon loss of SASS6 in mouse embryonic stem cells in vitro [57].…”
Section: What Was Found At Division Poles Of Bovine Blastomeres?mentioning
confidence: 71%
“…This may mean that formation of the first centrioles during early embryonic development in cattle can occur despite SAS6 protein deficiency. Structurally similar individual triplets that do not form centrioles were also found upon loss of SAS6 in mouse embryonic stem cells in vitro (Grzonka, Bazzi, 2022).…”
Section: Discussionmentioning
confidence: 86%
“…SASS6 is thought to be crucial for mitosis (Blomen et al, 2015; Dammermann et al, 2004; Leidel et al, 2005), and total loss of function would be embryolethal in humans. Marta Grzonka et al reported that Sass 6‐null mouse embryos lack centrioles, have an active mitotic surveillance cell death pathway, and arrest development at mid‐gestation (preprint) (Grzonka & Bazzi, 2022). Bergwell et al revealed that homozygotes for the SASS6 (L69T) variant (the same variant in Family 1) exhibit an increased failure of centrosomal duplication in a sensitized genetic background C. elegans but not wild‐type background, indicating that the defects attributed to the variant may be mild (Bergwell et al, 2023).…”
Section: Discussionmentioning
confidence: 99%